COMMON IN HEREDITARY DISEASES CONGENITAL HEART DEFECTS AND THEIR INDICATORS - Khudoykulova Nasiba Ismailovna (Zeta Repository, 2023)
Carried out an epidemiological study on the prevalence of congenital anomalies of malformations, (CAM) in Bukhararegion for the period from 2019 to 2021. It was shown that these CAMs as congenital heart defect and Down’s syndrome were the most common pathology among other CAMs.